P.arg102ser is a common Pde6? mutation causing autosomal recessive retinitis pigmentosa in Pakistani families - Anosha Ali Khan; Yar Muhammad Waryah; Muhammad Iqbal; Hafiz Muhammad Azhar Baig; Muhammad Rafique; Ali Muhammad Waryah (Journal of the Pakistan Medical Association, 2020)
Aim: To explore the genetic cause of autosomal recessive retinitis pigmentosa in consanguineous families. Methods: The multi-centre study was conducted from July 2015 to June 2018 at Liaquat University of Medical and health Sciences, Jamshoro, the University of Sindh, Jamshoro, and Islamia University, Bahawalpur, Pakistan, and comprised families affected with non-syndromic autosomal recessive retinitis pigmentosa. Ophthalmological investigations were done to assess the fundus of the patients and the status of the disease. Pedigrees were drawn and family histories were recorded to find out the mode of inheritance. A 10cc sample of whole blood was obtained from each participant and deoxyribonucleic acid was extracted. Homozygosity mapping was performed using three short tandem repeat polymorphisms closely linked to phosphodiesterase 6A gene, and the linked families were Sanger-sequenced for identification of the mutation. Bioinformatic tools were used to design amplification refractory mutation system assay and to assess the protein structure and pathogenic effects of the mutation. Results: In the 80 consanguineous families, there were 464 individuals, and, of them, 236(51%) were affected with their age ranging between 4 and 80 years. Family history and pedigree drawings revealed autosomal recessive retinitis pigmentosa with early childhood onset. Linkage analysis indicated the homozygosity in 6(7.5%) families. Sanger-sequencing revealed a common mutation c.304C>A (p.Arg102Ser); segregating with the disease in the linked families. Conclusion: The findings may offer effective genetic counselling and minimise disease penetration in consanguineous families. Key Words: PDE6a mutations, Retinitis pigmentosa, Pakistan, ARMS assay. Continuous...